Erik Gustaf Geijers instrumentalmusik i handskrift. En bestämning av autografer - af Geijerstam, Claes (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1988)
Erik Gustaf Geijer (1783-1847) was one of the leading personalities in Sweden during the early Romantic period. As historian and philosopher he had enormous influence; and through his musical and literary activities he became also a dominating figure in cultural circles in Uppsala in the first half of the nineteenth century. As a composer Geijer was largely self-taught. It was chiefly through assiduous piano playing that he acquired a thorough knowledge of the musical currents of his day. This knowledge helped him to compose songs and instrumental music of no mean quality. Whereas most of Geijer’s songs were printed and published in music-book form, only a very few of his instrumental works were published. Consequently most of the instrumental compositions exist only in handwritten copies of the individual instrumental parts or as handwritten scores. The extant manuscripts raise a number of questions. A central issue is how much of this material consists autographs, written in Geijer’s own hand, and how many manuscripts are copies. This essay is an attempt to clarify some of these issues. Geijer’s instrumental music is the main subject of this study. This does not mean that the vocal manuscripts have not been examined. A large number of song manuscripts have been used as a reference material, to be precise, all the Geijer songs in the Uppsala University library (UUB), which contains by far the largest and most important collection of manuscripts of Geijer’s music. The main part of the essay consists of a graphological examination of a selection of ”established” autographs which have been identified by using the music itself as the point of departure. This material includes unquestionably examples of working-progress. This is evident from the fact that the manuscripts in question are full of deletions and alterations. From seventeen selected autographs a system has been evolved for examining Geijer’s handwriting. This method has then been applied to the material as a whole. The essay concludes with a list of Geijer’s instrumental works arranged according to their character as autographs or as manuscript copies. Also included is a list of vocal manuscripts in the Uppsala University library collection which may be regarded as autographs.